Tailoring electronic and optical properties of TiS₂: Showcasing a DFT analysis of the substitutional doping effects with Li, Mg, O, and F - Mohd Noor, Nurfarhana; Chan, Kar Tim; Azis, Raba’ah Syahidah; Shabdin, Muhammad Kashfi; Hassan, Ahmed Jaber; Abdul Razak, Wan Mohammad Zulkarnain (Elsevier B.V., 2026)
Titanium disulfide (Formula presented) one of transition metal dichalcogenides (TMDs), have attracted attention due to its unique structural and optical characteristics. These characteristics make it a potential material for applications such as energy storage, optoelectronic and light-harvesting technologies. Using Li, Mg, O, and F as dopants, we conducted a thorough first-principles study of the electrical and anisotropic optical properties of both pristine and substitutionally doped (Formula presented). Our results show that doping causes (Formula presented) to go from semi-metallic to degenerate semiconducting and semiconducting behaviour. Among the studied dopant system, O doped (Formula presented) has excellent stability with (Formula presented) formation energy, low indirect bandgap, strong visible light absorption with (Formula presented) and high extinction coefficient (2.596). In contrast, other doped (Formula presented) like Li, Mg and F doped (induce degenerate semiconducting behaviour), have pronounce high value of electron loss function (ELF) in UV regions with 19.09, 14.30 and 10.28 respectively. This indicates strong plasmonic excitation which enhance UV light absorption basically for Li, Mg and F doped system (more than (Formula presented) ). This suggests their potential in electromagnetic interference (EMI) shielding, UV optoelectronic devices and solar-driven thermal applications.